Women's database directory: Latin America and Caribbean Women's Health Network (ISIS International SantiagoCL, 1992)
Contains information about many of the groups and organizations working on women's health issues from different perspectives around the world and especially in the Latin American/Caribbean region. Aims to identify and describe the subject and geographic areas, objectives, target groups and publications of the different organizations and groups.
DC